Students' Perceptions of Using the OpenAI ChatGPT Application in Improving Writing Skills - Zebua, Joice Angela Zebua; Katemba, Caroline Victorine (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study investigates the perceptions of utilizing the ChatGPT OpenAI application to enhance students' writing skills. One rapidly developing AI application is ChatGPT, a language model that can assist in writing. The purpose of this study is to explore students' perceptions of using the OpenAI ChatGPT application to improve their writing skills. This research uses a quantitative approach with data collection through a Likert-type closed questionnaire. A total of 82 students from various study programs at Universitas Advent Indonesia who have been using OpenAI ChatGPT for a minimum of four months were respondents in this study. The results show that the majority of respondents have a positive perception of using OpenAI ChatGPT to enhance learning motivation (41.25%), provide comprehensive and easy-to-use features (41%), and help correct grammar errors in writing articles (35.25%). However, some respondents feel neutral about OpenAI ChatGPT's ability to provide explanations that can improve writing skills (37.50%). It can be concluded that the use of OpenAI ChatGPT can be a useful tool in improving students' English writing skills. This study also indicates the potential for further development in providing more in-depth explanations.